Dialogues - Lynam, Ava; Huang, Huang; Abels, Sigrun; Yang, Guiqing (Urban-Rural Assembly (URA), 2023)
The URA periodical is an annual open-access publication, which will accompany the Sino-German research and development project Urban-Rural Assembly (URA, 01LE1804A-D), sponsored by the German Federal Ministry of Education and Research (BMBF) as part of the FONA program Sustainable Development of Urban Regions (NUR). By combining scientific texts and essays, photographic works, and/or ethnographic studies including interviews, spatial mapping and drawings, the URA periodical will seek to bridge academic, practice and policy discourses around global sustainability challenges and integrated planning and governance approaches at the urban rural interface.